Keanekaragaman Jenis Kepiting (Decapoda: Brachyura) di Sungai Opak, Daerah Istimewa Yogyakarta - Rury Eprilurahman; Wahyu Tejo Baskoro; Trijoko T (Biogenesis: Jurnal Ilmiah Biologi, 2015)
Crabs has been known inhabiting diverse habitat. Crabs were found in the sea, and some other species were found in terrestrial or freshwater. Crabs is one of the important biotic components of the aquatic ecosystem as detrivore. Opak River is one of the major rivers in the Daerah Istimewa Yogyakarta (DIY), which has a various conditions and direct impact on biodiversity including the diversity of crabs. Up to now, there is no database of crab species from Yogyakarta. The aim of this research was to determine the diversity of crabs from Opak River. Research were carried out for 5 months between June and October 2013. Samples were characterized and identified morphologically. The results show that there are five species of crabs in Opak River. Parathelphusa convexa (De Man, 1879) was commonly found from upstream to downstream. Varuna litterata (Fabricius, 1798) was found in downstream to estuary (brackish water). The other three species were only found in the estuary area viz. Ocypode ceratophthalma (Pallas, 1772), Episesarma versicolor (Tweedie, 1940), and Scylla serrata (Forsskål, 1775). It can be concluded that diversity of crabs in the Opak River estuary area is higher than the upstream and downstream areas.Keywords: brachyuran, crabs, diversity, morphology, Opak River